Pengaturan Kerja Fleksibel: Dampaknya terhadap Ketahanan Mental dan Kesejahteraan Generasi X, Y, dan Z di Depok - Susilowati, Endang; Kasali, Rhenald; Chotib , Chotib (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2024)
This research uses a quantitative approach by taking a sample of 150 respondents, consisting of Gen X, Y and Z, each with a total of 50 people in Depok City. The age range of Gen X is those born in 1965-1976 Gen Y was born in 1977-1994 while Gen Z was born in 1995-2010. This research wants to analyze the extent of the respondents' mental resilience in terms of daily work activities that are flexible (Flexible Working Arrangement) with physical and psychological well-being (Wellbeing). The results of the FWA study show that I feel more comfortable working with flexible working hours arrangements that are important work targets are achieved, and WELLBENG shows that a balanced work time arrangement with daily life will increase the money I save. Thus it can be concluded based on the findings contained in the hypothesis that there is a relationship between Flexible Working Arrangement and Wellbeing positively as evidenced by a score of 11.14.